TRANSLATION OF ECOLOGICAL TERMS FROM ENGLISH INTO UZBEK: CHALLENGES AND STRATEGIES - Saliyeva Z.; Norboev A. (Journal of new century innovations, 2024)
Translating ecological terminology from English into Uzbek presents a series of linguistic and cultural challenges. This article examines these challenges and proposes strategies to ensure accurate and effective translation. By addressing lexical gaps, structural differences, and cultural nuances, translators can enhance the clarity and relevance of ecological communication. The article also highlights best practices and methodologies for overcoming these challenges, ensuring that ecological information is accessible and understandable for Uzbek learners.